Innovation technologies in training specialists in engineering materials science - Duriagina, Zoya; Bohun, Lidiya; Pleshakov, Eduard; Tepla, Tetiana (Publishing House of Lviv Polytechnic National University, 2015)
The aim of educational program TEMPUS is the integration of Eastern countries in the Bologna process. Participating of Lviv Polytechnic National University in project “Modernization of two cycles (MA, BA) of competence-based curricula in Material Engineering according to the best experience of Bologna Process – 543994-TEMPUS-1-2013-1-BE-TEMPUS-JPCR” allows to improve the quality of training of specialists in the field of materials science. Directions of “MМATTENG” project realization by Applied Material Science and Materials Engineering chair, implementation of computer-integrated technologies within the project, formation of modernized educational programs, trainings and retrainings of lecturers, seminars on the base of EU Universities, enterprises and companies-developers of software products and formation of the common research centers of materials science with participation of leading foreign and home companies are described in this article.